2015
DOI: 10.1371/journal.pone.0142753
|View full text |Cite
|
Sign up to set email alerts
|

miRLocator: Machine Learning-Based Prediction of Mature MicroRNAs within Plant Pre-miRNA Sequences

Abstract: MicroRNAs (miRNAs) are a class of short, non-coding RNA that play regulatory roles in a wide variety of biological processes, such as plant growth and abiotic stress responses. Although several computational tools have been developed to identify primary miRNAs and precursor miRNAs (pre-miRNAs), very few provide the functionality of locating mature miRNAs within plant pre-miRNAs. This manuscript introduces a novel algorithm for predicting miRNAs named miRLocator, which isbased on machine learning techniques and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…19 Although the latest encouraging research has reported that up-regulated ZFAS1 acts as a promoter for the occurrence of NPC through the activation of the Wnt/β-catenin pathway, the role of ZFAS1 in NPC requires further investigation. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…19 Although the latest encouraging research has reported that up-regulated ZFAS1 acts as a promoter for the occurrence of NPC through the activation of the Wnt/β-catenin pathway, the role of ZFAS1 in NPC requires further investigation. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation. [21][22][23] Multiple miRNAs including miR-1, miR-let-7 and miR-138 participate in the tumorigenesis, progression and metastasis of NPC through biological functions, such as inducing apoptosis and inhibiting proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…There are several tools for in silico miRNA identification such as miRanalyzer, miR-PREFeR, miRTRAP, miRLocator, and MIReNA (Hendrix et al, 2010; Mathelier and Carbone, 2010; Hackenberg et al, 2011; Lei and Sun, 2014; Cui et al, 2015). Majority of these methods rely on the sequence information of previously validated miRNA and non-miRNA sequences such as genes (Friedländer et al, 2008; An et al, 2013), while others perform de novo prediction (Yousef et al, 2006; Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…miRLocator is a software based on machine-based learning which correlate the sequence and structural patterns extracted from miRNA:miRNA* duplexes (Cui et al 2015a). The software is also compatible enough to distinguish between the few real miRNAs and the large number of pseudo miRNAs.…”
Section: Mirlocatormentioning
confidence: 99%
“…Leclercq et al (2013) reported the use of miRduplex (miRdup) (http://www.cs.mcgill.ca/*blanchem/mirdup/) as an efficient tool for the computational prediction of locating miRNAs within their pre-miRNAs. Ten-fold cross-validation of 5854 experimentally validated miRNAs across 19 plant species highlighted the fact that miRLocator is a better option in predicting mature miRNAs within plant pre-miRNAs than miRdup (Cui et al 2015a).…”
Section: Mirlocatormentioning
confidence: 99%
See 1 more Smart Citation